Preclinical atherosclerosis at the time of pre‐eclamptic pregnancy and up to 10 years postpartum: systematic review and meta‐analysis. (January 2017) - Milic, N. M.; Milin‐Lazovic, J.; Weissgerber, T. L.; Trajkovic, G.; White, W. M.; Garovic, V. D.
Abstract : This article's abstract has been translated into Spanish and Chinese. Follow the links from theabstract to view the translations. ABSTRACT: Objectives: Pre‐eclampsia (PE) is a pregnancy‐specific hypertensive disorder that has been associated with cardiovascular risk factors and vascular changes, such as acute atherosis in placental blood vessels, similar to early‐stage atherosclerosis. The objective of this study was to determine whether women with PE have increased atherosclerotic burden, as determined by the carotid intima–media thickness (CIMT), compared with women without PE. Methods: We conducted a systematic review and meta‐analysis of studies that reported CIMT, a non‐invasive, ultrasound‐based measure of subclinical atherosclerosis, in women who did vs those who did not have PE. Studies were eligible if they had been conducted during pregnancy or during the first decade postpartum, and if CIMT was measured in the common carotid artery. Studies published before 7 March 2016 were identified through PubMed, EMBASE and Web of Science. Two reviewers used predefined forms and protocols to evaluate independently the eligibility of studies based on titles and abstracts and to perform full‐text screening, data abstraction and quality assessment. Heterogeneity was assessed using the I 2 statistic. Standardized mean difference (SMD) was used as a measure of effect size. Results: Fourteen studies were included in the meta‐analysis. Seven studies were carried out during pregnancy complicated by PE, 10 were carried out up to 10 years postpartum and three included measurements obtained at both time periods. Women who had PE had significantly higher CIMT than did those who did not have PE, both at the time of diagnosis (SMD, 1.10 (95% CI, 0.73–1.48); P < 0.001) and in the first decade postpartum (SMD, 0.58 (95% CI, 0.36–0.79); P < 0.001). Conclusions: Atherosclerotic load is present at the time of PE and may be a mechanism associated with the disease. Measurement of CIMT may offer an opportunity for the early identification of premenopausal women with atherosclerotic burden after a PE pregnancy. Copyright © 2016 ISUOG. Published by John Wiley & Sons Ltd. RESUMEN Objetivos: La preeclampsia (PE) es un trastorno hipertensivo específico del embarazo que ha sido asociada con factores de riesgo cardiovascular y cambios vasculares, tales como aterosis aguda en los vasos sanguíneos de la placenta, similares a las primeras etapas de la aterosclerosis. El objetivo de este estudio fue determinar si las mujeres con PE han aumentado la carga aterosclerótica, según lo determinado por el espesor del complejo íntima‐media de la arteria carótida (CIMT, por sus siglas en inglés), en comparación con las mujeres sin PE. Métodos: Se realizó una revisión sistemática y un metaanálisis de estudios que reportaron el CIMT, una medida no invasiva de la aterosclerosis subclínica obtenida mediante ecografía, comparando mujeres con PE y mujeres sin ella. Solo se incluyeron estudios llevados a cabo durante el embarazo o durante la primera década después del parto, y en los que se midió el CIMT en la arteria carótida común. Se usaron las bases de datos de PubMed, EMBASE y Web of Science para identificar estudios publicados antes del 7 marzo de 2016. Dos revisores utilizaron formularios y protocolos preestablecidos para evaluar de forma independiente la elegibilidad de los estudios, a partir de los títulos y los resúmenes, y para realizar un cribado del texto completo, un resumen de los datos y una evaluación de calidad. La heterogeneidad se evaluó mediante el test estadístico I 2 . Se usó la diferencia de medias estandarizada (SMD, por sus siglas en inglés) como una medida de la magnitud del efecto. Resultados: En el metaanálisis se incluyeron catorce estudios. Siete de los estudios se llevaron a cabo durante embarazos complicados por PE, 10 se realizaron hasta 10 años después del parto y tres incluyeron mediciones tomadas en ambos períodos. Las mujeres con PE tuvieron un CIMT significativamente mayor que aquellas que no la tenían, tanto en el momento del diagnóstico (SMD 1, 10 (I 95%, 0, 73‐1, 48), P <0, 001) como en la primera década después del parto (SMD 0, 58 (IC 95%, 0, 36‐0, 79), P <0, 001). Conclusiones: La carga aterosclerótica está presente en el momento de la PE y podría ser un mecanismo asociado con esta enfermedad. La medición del CIMT puede ofrecer una oportunidad para la identificación temprana de mujeres premenopáusicas con carga aterosclerótica después de un embarazo con PE. 目的 : 子痫前期(pre‐eclampsia, PE)是一种妊娠期特发的高血压疾病, 与心血管危险因素和血管改变有关, 如胎盘血管急性动脉粥样硬化, 与早期动脉粥样硬化相似。本研究的目的是通过检测颈动脉内—中膜厚度(carotid intima–media thickness, CIMT), 确定妊娠合并PE与无合并PE患者相比, 动脉粥样硬化负担是否增加。 方法 : 我们对报道PE患者与无PE患者相比CIMT的研究进行系统综述和meta分析, CIMT为无创性、基于超声的亚临床动脉粥样硬化检测方法。纳入标准为:研究在妊娠期间或产后头10年进行并检测颈总动脉的CIMT。检索PubMed、EMBASE和Web of Science中发表的研究, 时间截止至2016年3月7日。由两名人员根据预定的格式和方案, 通过题目和摘要独立评估符合纳入标准的研究, 并进行全文筛查、数据提取和质量评估。采用 I 2 检验评估异质性。采用标准化均数差(SMD)检测效应量。 结果 : meta分析中纳入14项研究。7项研究在妊娠合并PE时进行, 10项研究在产后10年进行, 3项研究在两个时间段均进行了检测。PE患者与无合并PE患者相比, 确诊时[SMD, 1.10(95% CI, 0.73~1.48); P <0.001]以及产后头10年[SMD, 0.58(95% CI, 0.36~0.79); P <0.001] CIMT均明显较高。 结论 : PE时存在动脉粥样硬化负担, 它可能与疾病发病机制有关。通过检测CIMT, 可以早期识别PE妊娠后存在动脉粥样硬化负担的绝经前女性。